(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
Introduction: Lymphnodes are common site of metastases for different cancers. Thus, clinical recognition and urgent diagnosis of palpable lymphadenopathy is of paramount importance; specially to differentiate between inflammatory lesions from neoplastic lesions. Fine needle aspiration cytology (FNAC) of the lymph node is a simple diagnostic tool to diagnose suspected and unsuspected lymph node malignancy.Aims–To find out the role of FNAC in the diagnosis of metastatic lesions of lymphnode and whenever possible, for typing of tumor.Material &Method– A total 900 patients, who presented with lymphadenopathy were studied at AMC MET medical College and L.G hospital, Ahmedabad, Gujarat for a period of 2 years. FNAC of enlarged lymphnode was performed and stain with hematoxylin and eosin.Results– Out of total 900 cases studied, 785 were benign and 95 were malignant lesions. Twenty cases were inconclusive. Among the malignant lesions, 80 cases were found to be metastatic lesions. Maximum numbers of metastatic lesions were found in cervical lymphnodes and metastatic squamous cell carcinoma was the most common lesion followed by metastatic adenocarcinoma.Conclusion– FNAC is a simple, rapid, accurate and non-expensive diagnostic technique which can be used for the initial diagnosis of metastatic lymphadenopathy. It can give significant clue to detect the primary site of the tumor in cases with hidden malignancy, who are presented with metastatic lymphadenopathy as an initial sign. Therefore, FNAC is a useful tool in diagnosing metastatic lesion of lymphnodes.